Are Women More Likely to be Credit Constrained? Evidence from Low-Income Urban Households in the Philippines - Malapit, Hazel Jean L. (Taylor and Francis, 2013)
Based on survey data for 2002 and 2006, this paper investigates the determinants of credit constraints among women and men in two urban slum communities of Manila in the Philippines. The results show that women are more likely to be credit constrained than men. Rather than wealth, informal lenders seem to rely more on reputation and credit history to screen prospective borrowers, and the consequences of repayment delays or defaults are more severe for women than for men. These findings provide empirical support for women-targeted credit interventions in urban poor contexts, particularly those that enable women to build and capitalize on good credit histories.